Criteria of assessment of short track runners' prospects as mean of promising sportsmen losses' prevention at selection stage - S.A. Kugayevskiy (H.S. Skovoroda Kharkov National Pedagogical University, 2015)
Purpose: to offer main criteria for assessment of short track runners' prospects. Material: 8 sportsmen of short track Ukrainian national team participated in the research. Influence of training means' volume on result, shown on competition distance, was determined. Both organism's functional and reserve potentials were assessed with the help of computer program D&K-test. Results: we have determined priority of functional indicators in selection of short track runners and for assessment of their prospects. Sportsman's potentials shall be assessed on the base of functional fitness indicators, analysis of competition practice and training process data of pervious stage of sport perfection. Conclusions: individualization of training process, considering physiological characteristics of definite sportsman, will permit to completely open the embedded potential. Absence of sportsman's progress with prominent functional system's characteristics points at demand in correction of training program for his sportsman.